2017
DOI: 10.3389/fnmol.2017.00428
|View full text |Cite
|
Sign up to set email alerts
|

DFNB1 Non-syndromic Hearing Impairment: Diversity of Mutations and Associated Phenotypes

Abstract: The inner ear is a very complex sensory organ whose development and function depend on finely balanced interactions among diverse cell types. The many different kinds of inner ear supporting cells play the essential roles of providing physical and physiological support to sensory hair cells and of maintaining cochlear homeostasis. Appropriately enough, the gene most commonly mutated among subjects with hereditary hearing impairment (HI), GJB2, encodes the connexin-26 (Cx26) gap-junction channel protein that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 199 publications
(276 reference statements)
2
64
0
1
Order By: Relevance
“…The affected individuals in this study, however, display a congenital bilateral severe-to-profound HI profile. This is consistent with knock-out mice (Koo et al 2009; Steffes et al 2012), but also similar to other HI genes that express both an autosomal dominant and recessive inheritance (Liu et al 1998; del Castillo and del Castillo 2017). Compared to the knock-out mouse, we did not observe any vestibulocochlear malformations in affected individual IV:1, assessed via CT-imaging.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The affected individuals in this study, however, display a congenital bilateral severe-to-profound HI profile. This is consistent with knock-out mice (Koo et al 2009; Steffes et al 2012), but also similar to other HI genes that express both an autosomal dominant and recessive inheritance (Liu et al 1998; del Castillo and del Castillo 2017). Compared to the knock-out mouse, we did not observe any vestibulocochlear malformations in affected individual IV:1, assessed via CT-imaging.…”
Section: Discussionsupporting
confidence: 88%
“…Variants in these genes that cause autosomal dominant forms of NSHI are often missense variants which exert a dominant negative effect on the activity of the wild-type protein or its close interactors (Liu et al 1998; del Castillo and del Castillo 2017). The autosomal dominant forms of NSHI are usually less severe, show more variability in phenotype, and are later in onset and progressive in nature compared to their recessive counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 200 GJB2 pathogenic mutations have been reported so far [4]. A number of missense mutations may lead to autosomal dominant non-syndromic hearing loss DFNA3 and autosomal dominant syndromic hearing loss associated with hyperproliferative epidermal disorders [5,6]. On the other hand, a majority of GJB2 mutations are inherited in a recessive form and lead to non-syndromic hearing loss DFNB1.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is also evidence that intolerance to redox stress also plays a role in acceleration of presbycusis among mice and humans. In an exemplary investigation by Fetoni et al, the authors generated an animal model of presbycusis using Gjb2± mice as a model of heterozygous human carriers of 35 del G. Variants in GJB2 , which in codes for gap junction protein connexin 26, are well described and include a large number of deafness‐related mutations (Del Castillo & Del Castillo, ; Zelante et al, ), the majority of which cause nonsyndromic autosomal recessive deafness type 1A (DFNB1A, OMIM6 220290), which accounts for approximately half of nonsyndromic autosomal recessive hearing loss (Kenna, Kimura, Paul, & Adams, ). Fetoni et al () found that Gjb2± mice demonstrated accelerated ARHL and found that these mice demonstrated significant apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, and deregulated expression of genes whose transcriptional control is regulated by nuclear factor erythroid 2‐related factor 2 (Nrf2), a crucial determinant of cellular tolerance to redox stress.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%